The Role of Teacher Behavior, Motivation and Emotion in Predicting Academic Social Participation in Class - Sánchez Rosas, Javier; Takaya, Paula Belén; Molinari, Alicia Verónica (Pensando Psicología, 2016)
Introduction: Academic social participation addresses student engagement behaviors that involve social interactions with peers and teachers. Objective: Perceived teacher behavior, task value, academic self-efficacy, class enjoyment and shame’s role in predicting academic social participation was analyzed. Method: Psychology students from a large national university completed self-report questionnaires assessing the model variables. A proposed model was evaluated by path analysis. Results: Model showed good fit to the data, explaining 31% of variance. Positive influences were detected of perceived teacher behavior on task value (β = 0.42), academic self-efficacy (β = 0.19), and class enjoyment (β = 0.24); of task value on class enjoyment (β = 0.52); and of class enjoyment on academic social participation (β = 0.44). Academic self-efficacy negatively affected class shame (β = -0.38), while class shame (β = -0.44) and task value (β = -0.24) showed a negative influence on academic social participation. Conclusion: Utility of modifying teacher behavior and motivation as a means to affect emotion was demonstrated. Class enjoyment and shame were the stronger predictors of academic social participation. Individual variables’ importance in moderating contextual influence on engagement was suggested.